2020
DOI: 10.1175/jhm-d-19-0292.1
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Forecasting without Models

Abstract: The authors explore persistence in streamflow forecasting based on the real-time streamflow observations. They use 15-min streamflow observations from the years 2002 to 2018 at 140 U.S. Geological Survey (USGS) streamflow gauges monitoring the streams and rivers throughout Iowa. The spatial scale of the basins ranges from about 7 to 37 000 km2. Motivated by the need for evaluating the skill of real-time streamflow forecasting systems, the authors perform quantitative skill assessment of persistence schemes acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…We used persistence-based predictions as reference to assess the DA-based prediction results. The persistence method incorporates streamflow observations from the same upstream stations used in DA and its concept is rather simple but efficient (e.g., Krajewski et al 2020). We found that DA outperforms persistence, particularly at catchment scales smaller than 5,000 km 2 (the number might be different at different regions depending on the configuration of stream gauge network), where the coverage fraction is not as good as the one for larger scales as shown in Figure 5c.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We used persistence-based predictions as reference to assess the DA-based prediction results. The persistence method incorporates streamflow observations from the same upstream stations used in DA and its concept is rather simple but efficient (e.g., Krajewski et al 2020). We found that DA outperforms persistence, particularly at catchment scales smaller than 5,000 km 2 (the number might be different at different regions depending on the configuration of stream gauge network), where the coverage fraction is not as good as the one for larger scales as shown in Figure 5c.…”
Section: Discussionmentioning
confidence: 93%
“…Persistence leads to underestimations in volume and peak discharge, and early peak timing, as illustrated in Figure 3; drainage areas (represented by single or multiple upstream gauging stations) that are smaller than the area represented by the downstream evaluation station yield the observed underestimations and early peak. However, the overall performance (KGE) of persistence seems better at many locations than that of model simulation with NoDA, implying that the forecasting approach without models can provide useful guidance if there are reliable gauging stations upstream (see Krajewski et al 2020). Overall, the NWM with DA outperforms persistence and NoDA based on KGE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a benchmark in hydrology, persistence forecast is also known as a hard to beat model for large watersheds at short to medium forecast range. Many studies suggest that persistence can be an alternative for evaluating future estimates of streamflow at short to medium range (Ghimire and Krajewski, 2020;Krajewski et al 2020).…”
Section: Performance Benchmarksmentioning
confidence: 99%
“…There is no unique threshold value of KGE that fits all applications (Knoben et al, 2019). Krajewski et al (2020) considers that model provides good results if KGE > 0.5. A prior application of ELEMeNT also considers that results are reliable for a KGE > 0.5 (Liu 2020).…”
Section: Nitrate-n Loading Used For Calibrationmentioning
confidence: 99%